1996
DOI: 10.1093/oxfordjournals.ndt.a027361
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of erythropoietin on rat vascular smooth-muscle cell via a putative erythropoietin receptor

Abstract: The present report provides preliminary evidence in favour of a direct action of the hormone on vascular smooth muscle via a specific EpoR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 0 publications
0
56
0
2
Order By: Relevance
“…Epo is known to have effects not only in erythropoiesis and thrombopoiesis 21,22 but also on many other cells and tissues, including endothelial cells, 26 smooth muscle cells, 27,28 cardiomyocytes, 29 and kidney cells, 30 as well as neuroprotective and suppressive actions in ischemia-induced neuronal cell death as neurogenic and neuroprotective agents via antiapoptotic, neurotrophic, antioxidant, and angiogenic effects. 10,13,31,32 Our study, however, showed that brain weight was significantly reduced in the Epoetin-treated group as compared with Epo-bp-and ␣Epo-bp-treated groups ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Epo is known to have effects not only in erythropoiesis and thrombopoiesis 21,22 but also on many other cells and tissues, including endothelial cells, 26 smooth muscle cells, 27,28 cardiomyocytes, 29 and kidney cells, 30 as well as neuroprotective and suppressive actions in ischemia-induced neuronal cell death as neurogenic and neuroprotective agents via antiapoptotic, neurotrophic, antioxidant, and angiogenic effects. 10,13,31,32 Our study, however, showed that brain weight was significantly reduced in the Epoetin-treated group as compared with Epo-bp-and ␣Epo-bp-treated groups ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Functional EpoR expression has been documented in many nonhematopoietic cell types, including vascular endothelial cells (20), smooth muscle cells (21), skeletal myoblasts (22), cardiac myocytes (23), neurons (24), retinal photoreceptors (25), liver stromal cells (26), placenta (27), kidney (28), and macrophages (29). EpoR expression and signaling in hematopoietic tissues is essential for normal mammalian erythropoiesis during development.…”
Section: Expression and Function Of Epo And Its Receptormentioning
confidence: 99%
“…Erythropoietin (EPO), a cytokine that was originally identified as a hematopoietic factor, has been widely used for the treatment of anemia in patients with chronic kidney diseases for nearly 20 yr. 8 More recently, EPO was found to interact with its receptor, expressed in a great variety of nonhematopoietic cell types (e.g., neurons, 9 endothelial cells, 10 vascular smooth muscle cells, 11 cardiomyocytes, 12 mesangial cells, renal proximal tubular cells 13 ) to induce a range of cytoprotective cellular responses (mitogenesis, 13 angiogenesis, 14 promotion of vas-cular repair, 15 and inhibition of apoptosis 16,17 ), which are independent of EPO's effects on erythropoiesis. 18 Indeed, EPO was reported to attenuate renal injury in acute renal failure models in experimental animals with ischemia-reperfusion, 19,20 cisplatin, 21 and radiocontrast medium injuries.…”
mentioning
confidence: 99%